Ethics and the treatment as prevention strategy among transgender women living with HIV in Argentina. Issue 5 (4th May 2021) - Zalazar, Virginia; Aristegui, Ines; Socías, M. Eugenia; Cardozo, Nadir; Sued, Omar; Shannon, Kate; Duff, Putu
Abstract: While numerous ethical concerns have been voiced regarding HIV service scale-up strategies targeting key populations, few studies have examined these from the perspective of affected groups. This study therefore sought to understand transgender women's experiences and perspectives of targeted HIV services scale-up in the context of Argentina's Treatment as Prevention strategy. In 2016, 25 purposively selected transgender women living with HIV were interviewed by a peer research associate. Interviews were audio recorded, transcribed verbatim and analysed using participatory coding techniques. Findings suggest that procedures around informed consent, including the provision of full information in lay language and voluntariness, were lacking both pre- and post-HIV test. Further, many transgender women felt disrespected and disregarded by healthcare workers. While the majority of participants were unaware of Treatment as Prevention, once explained, most felt the approach was ethical overall, and helped improve equity in HIV service access. Study findings offer several community-driven suggestions to support patient rights and the ethical scale-up of HIV services for transgender women in Buenos Aires, including the need for training in and the provision of non-judgemental, gender-affirmative care and the inclusion of peer-navigators.